3-Dimensional Model to Study Apoptosis Induction of Activated Natural Killer Cells Conditioned Medium Using Patient-Derived Colorectal Cancer Organoids - Parseh, Benyamin; Khosravi, Ayyoob; Fazel, Abdolreza; Ai, Jafar; Ebrahimi-Barough, Somayeh; Verdi, Javad; Shahbazi, Majid (Frontiers in Cell and Developmental Biology, 2022)
Natural killer (NK) cells are innate lymphocytes that can kill tumor cells via different pathways, including the secretion of cytotoxic granules in immunological synapses and the binding of apoptosis-inducing ligands with cognate death receptors on tumor cells. These ligands are also soluble in NK cells conditioned medium (NK-CM). However, novel preclinical in vitro models are required for solid tumors such as colorectal cancer (CRC) to investigate apoptosis induction of activated NK-CM in a tissue-like structure. In the present study, we established a patient-derived CRC organoid culture system as a new tool for CRC research in the last decade. Tumor organoids were stained with hematoxylin and eosin (H&E) and compared with the original tumor taken from the patient. Goblet cell differentiation and mucus secretion were evaluated using periodic acid–Schiff and alcian blue histochemical staining. Moreover, tumor organoids were stained for CDX2 and Ki67 markers with immunohistochemistry (IHC) to investigate gastrointestinal origin and proliferation. Histopathological evaluations indicated tumor organoids represent patient tumor characteristics. Primary NK cells were isolated and characterized using CD56 marker expression and the lack of the CD3 marker. Flow cytometry results showed the purity of isolated CD3−and CD56 + NK cells about 93%. After further ex vivo expansion, IL-2-activated NK-CM was collected. Secretions of IFN-γ and TNF-α were measured to characterize activated NK-CM. Cytokines levels were significantly elevated in comparison to the control group. Soluble forms of apoptosis-inducing ligands, including TNF-related apoptosis-inducing ligand (TRAIL) and FasL, were detected by western blot assay. Colon cancer organoids were treated by IL-2-activated NK-CM. Apoptosis was assessed by Annexin V-FITC/PI staining and quantified by flow cytometry. In conclusion, despite the activated NK-CM containing apoptosis-inducing ligands, these ligands’ soluble forms failed to induce apoptosis in patient-derived colon cancer organoids. Nevertheless, we report a reliable in vitro assessment platform in a personalized setting.